PENGAMBILAN KEPUTUSAN DAN PERENCANAAN KBIJAKAN - Mahanum Mahanum (Universitas Dharmawangsa, 2021)
Planning has been recognized as the first function or step in management and applies at all levels of management. It also defines an organization’s goals and establishes a process for determining how the management system will achieve its goals, how it will get where it is going. The purpose of planning is to help organizations achieve their goals. Generally speaking, the higher the level of management, the more time in planning formal activi- ties. Formal planning is done on a regular time cycle by a group of people working together